2015
DOI: 10.7314/apjcp.2015.16.2.443
|View full text |Cite
|
Sign up to set email alerts
|

MMP2 Gene-735 C/T and MMP9 gene -1562 C/T Polymorphisms in JAK2V617F Positive Myeloproliferative Disorders

Abstract: Background: Myeloproliferative disorders (MPDs) are clonal hematologic malignancies originating at the level of the pluripotent hematopoietic stem cell. Matrix metalloproteases (MMPs) are proteolytic enzymes that contribute to all stages of malignancy progression. Genetic variants in the MMP genes may influence the biological function of these enzymes and change their role in carcinogenesis and progression. To our knowledge, this is the first investigation of associations between the -735 C/T and -1562 C/T pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…The MMP2-735C/T polymorphism is located in the promoter region of the MMP2 gene, and exhibits a substantial influence on transcriptional activity. MMP2-735C/T destroys the Sp1-binding element, with T allele characterized by decreased promoter activity [11]. MMP2 is the keystone part controlling the tumor invasion, growth and metastasis [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MMP2-735C/T polymorphism is located in the promoter region of the MMP2 gene, and exhibits a substantial influence on transcriptional activity. MMP2-735C/T destroys the Sp1-binding element, with T allele characterized by decreased promoter activity [11]. MMP2 is the keystone part controlling the tumor invasion, growth and metastasis [12].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researches reported that MMP-2 has poor prognostic effects in cancers especially in stomach [13], breast [14], lung [15], colorectal [16] and even ovarian cancers [17]. MMP-2 has an essential role in development of some hematologic malignancies [11] like myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML) where abnormal expression of MMP2 and even MMP9 were found [18]. Serum MMP9 levels may be useful in predicting prognosis and clinical outcomes of CLL patients in early periods [19].…”
Section: Introductionmentioning
confidence: 99%
“…Myeloproliferative neoplasms (MPN) have been previously called myeloproliferative disorders are chronic, clonal hematopoietic stem cell group of disorders characterized by enhanced proliferation of one or more myeloid lineage cells (Sag et al, 2015;Yang et al, 2015). Polycythaemia rubra vera (PV) is a indolent MPN characterized by an absolute increase in the number of red blood cells, usually accompanied by leukocytosis, thrombocytosis and splenomegaly (Ma et al, 2008;Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Myeloproliferative neoplasms (MPN) are a group of diseases which are characterized by excessive production of one or more myeloid lineage cells arising from genetic mutations in multipotential hematopoietic stem cells in bone marrow (Sag et al, 2015;Yang et al, 2015). Idiopathic Primary myelofibrosis (PMF) is a heterogenous Philadelphia chromosome-negative MPN exemplified by cytopenias, progressive marrow fibrosis; extramedullary hematopoiesis associated with excessive production of inflammatory cytokines and shortened survival.…”
Section: Introductionmentioning
confidence: 99%